ANCIENT SOFT WHEAT NEW GRAINS QUALITY INDICATORS SOUTHERN AGRICULTURAL SCIENTIFIC RESEARCH INSTITUTE - Diyor Turdikulovich Djuraev; Gulzor Kholmurodovna Aminova (Galaxy International Interdisciplinary Research Journal, 2023)
Selection of wheat genotypes that can accumulate the valuable iron contained in wheat grain more effectively, and to increase grain yield, as well as carrying out selection work aimed at improving its grain quality, baking properties and nutrition, is one of the most urgent tasks of today. In this article, the grain quality indicator of soft wheat varieties and the amount of iron in the grain are mentioned.